3, 5‐Dimethylorsellinic Acid Derived Meroterpenoids from Eupenicillium sp. 6A‐9, a Fungus Isolated from the Marine Sponge Plakortis simplex. Issue 1 (3rd January 2018) - Gu, Bin‐Bin; Wu, Wei; Liu, Li‐Yun; Tang, Jie; Zeng, Ya‐Jun; Wang, Shu‐Ping; Sun, Fan; Li, Lei; Yang, Fan; Lin, Hou‐Wen
Abstract : Two rare 6(D)/5(E) ring‐fused meroterpenoids, eupeniacetal A (1 ) and eupeniacetal B (2 ), and three new meroterpenoids, 1‐methoxy‐hydropreaustinoid A1 (3 ), hydroberkeleyone B (4 ), and 22‐deoxy‐10‐oxominiolutelide B (5 ), as well as five known meroterpenoids, 22‐deoxyminiolutelide B (6 ), preaustinoid A1 (7 ), berkeleyone C (8 ), berkeleyacetal A (9 ), and preaustinoid A3 (10 ), have been isolated, through the aid of LC–MS, from the sponge‐derived fungus Eupenicillium sp. 6A‐9. The structures of these meroterpenoids were elucidated by detailed spectroscopic analysis, comparison with literature data, and single‐crystal X‐ray diffraction. The absolute configurations were assigned by means of TDDFT/ECD and [ α ]D calculations as well as by X‐ray diffraction analysis. These compounds showed inhibitory activity towards TNF‐α production in the induced THP‐1 cell line but were inactive against normal tumor cell lines. Abstract : Five new 3, 5‐dimethylorsellinic acid derived meroterpenoids have been isolated from the fungus Eupenicillium sp. 6A‐9 derived from the marine sponge Plakortis simplex and their structures determined by spectroscopy, calculations, and X‐ray diffraction. The compounds showed inhibitory activity towards TNF‐α production in the induced THP‐1 cell line but were inactive against normal tumor cell lines.